The Effect of the Texture of Two Energy Bars on the Oral Processing of Cyclists: An Exploratory Study - Irene Jimenez-Perez; Arian Ramón Aladro-Gonzalvo; Antonio Vera Morán; Andrés Camacho-García; Alberto Encarnación-Martínez; Pedro Pérez-Soriano (Applied Sciences, 2023)
In cycling, a wide range of ergogenic foods with a variety of flavours, shapes, and textures are available. The timing of their consumption and their correct oral processing can influence the performance of athletes. Furthermore, the differences in the texture of energy bars could result in differences in the chewing required. Nonetheless, research in this area is still scarce. The aim of this study was to analyse how the consumption of two energy bars with different textures (viscous versus hard) influenced the variables of oral processing, pedalling intensity, and the perception of satisfaction among cyclists. Ten cyclists performed two 15 min sections on a cycle ergometer at a moderate intensity (120–130 W) and consumed one of the two energy bars at random in each of the sections. The results showed that a shorter chewing duration and a fewer number of chews were required to consume the softer bar (p < 0.05, ES > 0.7). However, no differences among the cyclists were observed in the intensity of pedalling or perception of satisfaction. Nevertheless, participants were able to distinguish between the two different textures while pedalling. In conclusion, the texture of energy bars altered the oral processing of cyclists but did not affect pedalling intensity or perception of satisfaction.